The Development of Environmental Productivity: the Case of Danish Energy Plants - Geraldine Henningsen; Arne Henningsen; Sascha T. Schröder; Simon Bolwig (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
The Danish "Klima 2020" plan sets an ambitious target for the complete phasing-out of fossil fuels by 2050. The Danish energy sector currently accounts for 40% of national CO2 emissions. Based on an extended Farrell input distance function that accounts for CO2 as an undesirable output, we estimate the environmental productivity of individual generator units based on a panel data set for the period 1998 to 2011 that includes virtually all fuel-fired generator units in Denmark. We further decompose total productivity into technical efficiency, best practice ratio, and scale efficiency and use a global Malmquist index to calculate the yearly changes. By applying time series clustering, we can identify high, middle, and low performance groups of generator units in a dynamic setting. Our results indicate that the sectoral productivity only slightly increased over the fourteen years. Furthermore, we find that there is no overall high achiever group, but that the ranking, although time consistent, varies between the different productivity measures. However, we identify steam turbines and combustion engines for combined heat and power production as potential high performers, while combustion engines that only produce electricity are clearly low performers.
Keywords: C50; D22; D24; O30; 330; Environmental productivity; energy sector; productivity analysis; CO2 mitigation; renewable energy; transition